PENGARUH BI RATE, RASIO KECUKUPAN MODAL, DAN NON-PERFORMING FINANCING TERHADAP LIKUIDITAS BANK UMUM SYARIAH DI INDONESIA TAHUN 2015 - 2019 - Yahya, Muhammad Ridwan; Jaharuddin, Jaharuddin (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to find out the influence of BI Rate, Capital Adequacy Ratio, and Non-Performing Financing Sharia Commercial Bank in 2015-2019 in Indonesia, using a quantitative associative case study approach. The data used in this study used secondary data by searching for data resources in journals, books, literature, and annual report by Sharia Commercial Bank on their website. The result showed that BI Rate by the partial method has a significant positive effect on liquidity, Capital Adequacy rate by the partial method has a significant positive effect on liquidity, and Non-Performing Financing by the partial method has a significant negative effect on liquidity, and BI Rate, Capital Adequacy Ratio, and Non-Performing Financing by simultan method have a significant positive effect on liquidity. Keywords : BI Rate, Capital Adequacy Ratio, Non-Performing Financing, Liquidity.